2001
DOI: 10.1302/0301-620x.83b7.10516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of displacement of fractures of the greater tuberosity on the mechanics of the shoulder

Abstract: Using a dynamic biomechanical model of malunion of the shoulder, we have determined the change in deltoid force required for abduction with various combinations of superior and posterior displacement of fractures of the greater tuberosity of the humerus. We tested eight fresh human cadaver shoulders in a dynamic shoulder-testing apparatus during cycles of glenohumeral abduction from 0 degrees to 90 degrees. The greater tuberosities were osteotomised and stabilised to represent malunion with combinations of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…16 Bono et al 5 showed that the abduction force is significantly increased by 16% and 27% by superior displacements of 0.5 and 1 cm, respectively, while combined superior and posterior displacement of 1 cm gives an increase in force of 29%. Thus, the objectives of surgical treatment are to prevent painful malunion and avoid alteration of the rotator cuff attachment to the proximal humerus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Bono et al 5 showed that the abduction force is significantly increased by 16% and 27% by superior displacements of 0.5 and 1 cm, respectively, while combined superior and posterior displacement of 1 cm gives an increase in force of 29%. Thus, the objectives of surgical treatment are to prevent painful malunion and avoid alteration of the rotator cuff attachment to the proximal humerus.…”
Section: Discussionmentioning
confidence: 99%
“…2 Current literature recommends surgical intervention in cases with >5 mm of displacement in the general population or >3 mm of displacement in active patients. 1,[3][4][5] Open surgeries or percutaneous techniques with the aid of fluoroscopy using suture anchors or screws are well accepted for the reduction and fixation of GT fractures. 1,6,7 However, the techniques continue to evolve, particularly minimally invasive and arthroscopic techniques that have the advantages of minimizing skin incision, soft tissue dissection, and associated morbidities.…”
mentioning
confidence: 99%
“…Posterosuperior displacement of the greater tuberosity of more than 5 mm from the anatomic position can result in malunion and impingement of the shoulder due to an altered rotator cuff insertion site influencing the motion in the glenohumeral joint (Bono et al 2001). The recommendation of Neer (2006) to treat displacements of the tuberosity of less than 1 cm nonoperatively has been revised, and in the current literature it is recommended that surgical fixation be used for fractures with more than 5 mm of displacement in the general population or more than 3 mm of displacement in active patients with frequent overhead activity (Park et al 1997, George 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The deltoid force required for abduction [4] is significantly higher when the greater tuberosity is displaced more than 0.5 cm.…”
Section: Introductionmentioning
confidence: 93%